2022
DOI: 10.1371/journal.pone.0264636
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial approach to understanding determinants of depression among men who have sex with men living with HIV: A systematic review

Abstract: Introduction Men who have sex with men (MSM) living with HIV are more likely to be depressed than MSM without HIV. The AIDS epidemic will not end if the needs of people living with HIV and the determinants of health are not being addressed. Compared to HIV individuals without depression, depressed HIV individuals have worse clinical outcomes and higher mortality risk. Depression is caused by a complex combination of social, psychological, and biological variables. This systematic review, thereby motivated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…According to previous research, the experience of HIV infection is a highly stressful event for individuals and is associated with co-occurring mental disorders [ 8 , 11 ]. The purpose of the present study was to assess the dimensions of forgiveness as predictors of quality of life in PLWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous research, the experience of HIV infection is a highly stressful event for individuals and is associated with co-occurring mental disorders [ 8 , 11 ]. The purpose of the present study was to assess the dimensions of forgiveness as predictors of quality of life in PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of psychiatric disorders in the seropositive population calls for research on psychosocial resources that may improve functioning in the face of experiencing a health crisis. HIV infection is a biopsychosocial phenomenon that affects not only physical health but also other aspects of PLWH’s lives, including occupational and social functioning, marriage and intimate relationships, and parenting [ 11 ]. Numerous conceptualizations suggest that biological, psychological, and behavioral factors interact in complex ways and influence the clinical progression of HIV-related diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While engaged in this cohort study, psychosocial vulnerabilities were not found to decrease significantly over time. This may be linked to the idea that the first year of moving to a new country, learning about one’s HIV diagnosis, and engaging in care and treatment, can be a very challenging time across the emotional, mental, and social levels for individuals [ 15 , 57 , 58 ]. Additionally, perhaps more time (e.g., over 1–2 years) is needed to see a change in these aspects of participants’ lives.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the determinants of depression in MSM communities include HIV-related stigma, unemployment, sleep disorders, smoking, racism against blacks, birth abroad, initiation of ART, and lack of access to mental health care. Aging, internalized stigma, and lack of self-efficacy, and social support are also important in this complication [ 55 , 90 , 91 ]. However, the prevalence of depression in MSM and other key populations can be influenced by the factors mentioned in the study of Mohamad Faisal et al [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging, internalized stigma, and lack of self-efficacy, and social support are also important in this complication [ 55 , 90 , 91 ]. However, the prevalence of depression in MSM and other key populations can be influenced by the factors mentioned in the study of Mohamad Faisal et al [ 90 ]. In this study, various factors were mentioned to be effective in increasing the incidence or prevalence of depression in the MSM community, the most important of which was their infection with infectious diseases, especially HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%